2005
DOI: 10.1007/s10519-005-9004-0
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Smoking Susceptibility Locus on Chromosome 11p12: Evidence from Sex-limitation Linkage Analyses in a Sample of Australian Twin Families

Abstract: Many twin studies have identified sex differences in the influence of genetic and environmental factors on smoking behaviors. We explore the evidence for sex differences for smoking initiation and cigarette consumption in a sample of Australian twin families, and extend these models to incorporate sex differences in linkage analyses for these traits. We further examine the impact of including or excluding non-smokers in genetic analyses of tobacco consumption. Accounting for sex differences improved linkage re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 55 publications
2
32
1
Order By: Relevance
“…Linkage studies have evaluated several smoking phenotypes, such as smoking initiation [120,178], the number of cigarettes smoked daily (smoking quantity) [92,96,95,120,165,182], nicotine dependence [50,96,95,98,165], and withdrawal severity [165], and overall, one or more regions in nearly all chromosomes have been implicated in smoking-related behaviors. Furthermore, nAChR subunit genes have been found within some of the loci identified in linkage studies, suggesting that these genes may warrant further investigation.…”
Section: Genome-wide Linkage Analysesmentioning
confidence: 99%
“…Linkage studies have evaluated several smoking phenotypes, such as smoking initiation [120,178], the number of cigarettes smoked daily (smoking quantity) [92,96,95,120,165,182], nicotine dependence [50,96,95,98,165], and withdrawal severity [165], and overall, one or more regions in nearly all chromosomes have been implicated in smoking-related behaviors. Furthermore, nAChR subunit genes have been found within some of the loci identified in linkage studies, suggesting that these genes may warrant further investigation.…”
Section: Genome-wide Linkage Analysesmentioning
confidence: 99%
“…39 Loci identified with other smoking phenotypes also contain some biologically interesting candidates, such as a region on chromosome 5q located near the dopamine receptor (D 1 ) gene, which has been reported in several studies. 32,40,41 Regions on chromosomes 6, 9 and 11 26,32,33,[40][41][42][43][44][45][46] are also promising as several studies have replicated the linkage and these regions contain some potential biologically relevant candidate genes (Table 1).…”
Section: Genome-wide Linkage Studiesmentioning
confidence: 99%
“…33 Genetic variation in DRD2 has been investigated; the TaqI A1 variant is a 32806 C4T substitution at 10 kb downstream of DRD2 and lies within a novel, as yet uncharacterized, kinase gene ANKK1. 58 Some studies, but not all, found the TaqI A1 allele resulted in a lower density of D 2 receptors in the human striatum in vitro and in vivo.…”
Section: Mk Ho and Rf Tyndale 86mentioning
confidence: 99%
See 1 more Smart Citation
“…However, ascertainment criteria as well as study samples have been diverse, and not surprisingly, only a few findings seem consistent across studies. Depending on the study population and the phenotype criteria used, some evidence of linkage (logarithm of the odds (LOD)/Z scores X2) for ND has been reported on chromosomes 2, 6, 7, 8, 10, 11 and 18, [10][11][12][13] linkage for smoking rate on chromosomes 3, 4, 5, 10, 11 and 17, 7,[12][13][14][15][16] and linkage for ever smoking, habitual smoking or smoking initiation on chromosomes 6, 9 and 11. 7,[16][17][18] Thus, suggestive findings for smoking-related loci exist for most chromosomes.…”
Section: Introductionmentioning
confidence: 99%